URBAN IDENTITY AND EMOTIONAL DISTANCE: HOFSTEDE’S CULTURAL VALUES DIMENSIONS ON APT BY BRUNO MARS AND ROSÉ - Ayu Saraswati (Universitas Negeri Surabaya, 2024)
This study examines the song APT by ROSÉ and Bruno Mars using Hofstede’s cultural value dimensions to analyze how the lyrics represent the complexities of urban life and cultural identity. The song’s metaphor of the apartment (아파트) symbolizes both physical closeness and emotional distance, highlighting the tension between collectivist and individualist values, power distance, uncertainty avoidance, femininity in modern cities. Through its bilingual lyrics, the song bridges cultural divides and addresses universal themes of emotional longing and isolation. The analysis reveals how the song challenges traditional norms, promoting egalitarian relationships and emphasizing spontaneity over stability, which contrasts with South Korea’s traditional high uncertainty avoidance. The conclusion of this analysis is APT offers insight into the evolving cultural dynamics of South Korea, showing how the song blends local and global influences while resonating with audiences through its exploration of connection, freedom, and modern relationships.